THE PHENOMENON OF LABOR EXPLOITATION: A SYSTEMATIC LITERATURE REVIEW - Andi Khafifah Nurul Isnaini A. Tagunu; Salahudin Salahudin (EMPATI: Jurnal Ilmu Kesejahteraan Sosial, 2023)
Abstract. This research aims to find out the issues of labor exploitation through the perspective of Marxism theory as Karl Marx's criticism of the development of capitalism and the impact of injustice in the distribution of wealth and social inequality. Labor exploitation raises the concept of division of labor on an international scale which in practice results in underdevelopment and dependence of poor countries on rich countries. This research uses the Systematic Literature Review method with 144 scientific articles sourced from the Scopus database. This article review uses the VOS viewer application. The results of this study reveal that the development of research related to the phenomenon of labor exploitation is very diverse as evidenced by workers who experience various exploitation in the workplace which can be classified in several schemes, namely criminal violations, human rights, denial of labor rights, labor trafficking, security violations and discrimination against economic violations. The research also shows that it is not only those with power who are responsible for exploitation, but also state authorities themselves. All research results contribute to the development of a research roadmap on labor exploitation as well as the development of science, especially socio-political science related to issues of labor exploitation, and the development of policies to deal with the phenomenon of labor exploitation in the world. The limitation of this research is that the articles used are only sourced from the Scopus database so that the research findings cannot describe the overall issue of labor exploitation in the world. Future research needs to use scientific articles sourced from other reputable international databases, such as Web of Science from Dimensions Scholars.  Keywords: Labor exploitation, labor, global capitalism, social inequality. Abstrak. Studi ini bertujuan mengetahui isu-isu eksploitasi tenaga kerja melalui perspektif teori Marxisme sebagai kritik Karl Marx atas perkembangan kapitalisme dan dampak ketidakadilan pada distribusi kekayaan serta kesenjangan sosial. Eksploitasi tenaga kerja memunculkan konsep pembagian kerja pada skala internasional yang pada praktiknya mengakibatkan keterbelakangan serta ketergantungan negara miskin terhadap negara kaya. Penelitian ini menggunakan metode Systematic Literature Review dengan 144 artikel ilmiah bersumber dari database scopus. Review artikel ini menggunakan aplikasi VOS viewer. Hasil penelitian ini mengungkapkan bahwa perkembangan penelitian terkait fenomena eksploitasi tenaga kerja sangat beragam terbukti dengan para tenaga kerja yang mengalami berbagai eksploitasi di tempat kerja yang dapat diklasifikasikan dalam beberapa skema yakni pelanggaran pidana, hak asasi manusia, penolakan hak tenaga kerja, perdagangan tenaga kerja, pelanggaran keamanan dan diskriminasi terhadap pelanggaran ekonomi. Penelitian ini juga menunjukkan bahwa bukan hanya yang memiliki kekuasaan yang bertanggung jawab atas eksploitasi, tetapi juga otoritas negara itu sendiri. Semua hasil penelitian berkontribusi pada pengembangan roadmap penelitian tentang eksploitasi tenaga kerja serta pengembangan ilmu khususnya ilmu sosial politik terkait isu-isu eksploitasi tenaga kerja, dan pengembangan kebijakan penanganan terhadap fenomena eksploitasi tenaga kerja di dunia. Keterbatasan penelitian ini adalah artikel yang digunakan hanya bersumber dari database scopus sehingga temuan penelitian tidak dapat menggambarkan secara keseluruhan tentang isu eksploitasi tenaga kerja di dunia. Penelitian berikutnya perlu menggunakan artikel ilmiah bersumber dari database internasional bereputasi lainnya, seperti Web of Science dari Dimensions Scholars. Kata Kunci: Eksploitasi tenaga kerja, buruh, kapitalisme global, kesenjangan sosial.